Effects of evaporative cooling greenhouse growing on flowering of Vanda - T. Sirisawad (2018)
Exporter of Vanda plant sometimes faced the problem of Vanda flowering which could not be controlled and sometimes it did not flower at the destination country. This may be caused by the inappropriate environmental conditions, nevertheless, the researches on this topic are rare. This research was aimed to determine the effects of duration in evaporative cooling greenhouse (ECG) on flowering of this plant. The experiment was carried out at H.M. The King's Initiative Centre for Flower and Fruit Propagation, Chiang Mai, Thailand, and Vanda Manuvadee which usually has very low flower productivity during March- July was used. Plants were cultivated in evaporative cooling greenhouse with average day/night temperature of 29.87±4.21/25.09±0.98°C for 2, 4, 6 and 8 weeks before being moved to natural condition (average 33.47±4.58/26.23±2.31°C day/night temperature), compared with those cultivated under natural condition throughout the experiment as control treatment. The results showed that the duration in evaporative cooling greenhouse increased the numbers of flower buds and affected the days to flowering, i.e., 2- and 4-week cooling treatments could increase flowering percentages, while growing for 6 and 8 weeks in cooling greenhouse delayed flowering. However, the number of floret, floret size, floret longevity, spike length and inflorescence longevity of the 2- and 4-week treatments were not significantly different from the control treatment. Furthermore, at the first-floret-opening stage, the total non-structural carbohydrate concentrations and contents in leaves increased in treatments of longer growing in ECG, which related to flowering delayed. Thus, those of the 8-week cooling treatment were higher than the others.